2017
DOI: 10.1177/1557988317735928
|View full text |Cite
|
Sign up to set email alerts
|

Fatherhood in Australian Aboriginal and Torres Strait Islander communities: An Examination of Barriers and Opportunities to Strengthen the Male Parenting Role

Abstract: Traditional Australian Aboriginal and Torres Strait Islander societies value men’s role as parents; however, the importance of promoting fatherhood as a key social determinant of men’s well-being has not been fully appreciated in Western medicine. To strengthen the Aboriginal and Torres Strait Islander male parenting role, it is vital to examine current barriers and opportunities. The first author (a male Aboriginal health project officer) conducted yarning sessions in three remote Australian communities, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 34 publications
3
70
0
1
Order By: Relevance
“…Moreover, the realms of Aboriginal and Torres Strait Islander male parenting remains underfunded and under-resourced, and as Panter-Brick et al (2014) suggests, men-only parenting services 'are often add-on to other programmes, and deemed unsustainable when resources are short' (Panter-Brick et al 2014, p. 1208. The lack of appropriate education, support programs and services available for Aboriginal and Torres Strait Islander male parents has not stopped this cohort of males from engaging in and wanting to fulfil their roles and responsibilities as parents (Jia 2000;Newell et al 2006; Males in Black Inc. and Uni-tingCare Wesley Port Pirie 2010; Parker 2010; Hammond 2011; Kurti et al 2013;Collard et al 2016;Fletcher 2017;Rossiter et al 2017;Reilly and Rees 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the realms of Aboriginal and Torres Strait Islander male parenting remains underfunded and under-resourced, and as Panter-Brick et al (2014) suggests, men-only parenting services 'are often add-on to other programmes, and deemed unsustainable when resources are short' (Panter-Brick et al 2014, p. 1208. The lack of appropriate education, support programs and services available for Aboriginal and Torres Strait Islander male parents has not stopped this cohort of males from engaging in and wanting to fulfil their roles and responsibilities as parents (Jia 2000;Newell et al 2006; Males in Black Inc. and Uni-tingCare Wesley Port Pirie 2010; Parker 2010; Hammond 2011; Kurti et al 2013;Collard et al 2016;Fletcher 2017;Rossiter et al 2017;Reilly and Rees 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Aboriginal and Torres Strait Islander men rarely rate a mention within discussions of parenting (Reilly and Rees 2018), unless framed in the negative (Stuart et al 2015) or as the cause of dysfunctional family life (Stoneham et al 2014). Contributing to this exclusion is a parenting domain, which is dominated by a narrative that tends to exclusively focus and privilege the roles and responsibilities of females (Astone and Peters 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Esto resta posibilidades al desarrollo de la capacidad de autonomía y toma de decisiones (61) . Estamos ante competencias y habilidades cognitivo-operativas que no solo han sido relacionadas con el crecimiento personal y el desarrollo de bienestar, sino también con la posibilidad de participar de manera efectiva como miembro activo de una comunidad (62,63,64) . En el caso concreto de programas como en el que se participó, esto contribuye a generar una respuesta instrumental y asistencialista, por parte de las familias aborígenes, para beneficiarse de una serie de recursos y gestiones que, en definitiva, pueden estar siendo una barrera para generar un mayor nivel de desarrollo humano y capacidad de integración social.…”
Section: Discussionunclassified
“…In addition, services often promote and provide ANC through a maternal lens. 28,29 These factors may result in men feeling marginalised and peripheral in accessing or engaging with ANC services. 1,8 For Aboriginal people in Australia, their role as parents and caregivers has experienced significant and sustained disruption through colonisation, forced removal from cultural homelands, government policies of removing children and enduring policies of displacement and discrimination.…”
mentioning
confidence: 99%
“…30 Recent qualitative research findings have demonstrated that Aboriginal men aspire to assume responsibility for fatherhood early, embody the notion of complementary caregiver and promote cultural pride in their children. [29][30][31]33 Amongst the studies exploring contemporary expressions and experiences of Aboriginal fatherhood, [29][30][31][33][34][35] Aboriginal men's journey through the ANC period remains underexplored. This study aimed to explore some Aboriginal men's perceptions of self and their intersection with ANC service providers during the ANC period.…”
mentioning
confidence: 99%